(untitled) (Texas Journal of Medical Science, 2024)
Ophthalmology, the branch of medicine concerned with the study and treatment of disorders and diseases of the eye, has evolved significantly over recent decades due to advances in technology, medical research, and public health initiatives. This article explores the current trends in ophthalmology, such as the growing adoption of minimally invasive surgeries, artificial intelligence (AI) applications, and telemedicine. It also addresses pressing challenges in the field, including the rising prevalence of eye diseases like cataracts, glaucoma, and age-related macular degeneration (AMD), as well as disparities in access to eye care in low-income regions. The article concludes by analyzing future prospects, including innovations in gene therapy, regenerative medicine, and global health policies aimed at improving vision health worldwide